2016
DOI: 10.1016/j.ophtha.2016.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography Vessel Density in Glaucomatous Eyes with Focal Lamina Cribrosa Defects

Abstract: Purpose To investigate whether vessel density assessed by optical coherence tomography angiography (OCT-A) is reduced in glaucomatous eyes with focal lamina cribrosa (LC) defects. Design Cross-sectional case-control study. Participants Eighty-two primary open angle glaucoma (POAG) patients from the Diagnostic Innovations in Glaucoma Study (DIGS) with and without focal LC defects (41 eyes of 41 patients in each group) matched by severity of visual field (VF) damage. Methods OCT-A-derived circumpapillary v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 42 publications
(68 reference statements)
1
96
1
5
Order By: Relevance
“…We tried to minimize this risk by not restricting the publication year. Second, in several studies a considerable number of patients were excluded because of poor image quality secondary to poor fixation, movement artifacts, or the presence of a visually significant cataract [6, 7, 16, 26, 34, 71, 95]. This potentially limits the clinical usefulness of OCTA in populations with cataract, macular lesions, and advanced glaucoma.…”
Section: Resultsmentioning
confidence: 99%
“…We tried to minimize this risk by not restricting the publication year. Second, in several studies a considerable number of patients were excluded because of poor image quality secondary to poor fixation, movement artifacts, or the presence of a visually significant cataract [6, 7, 16, 26, 34, 71, 95]. This potentially limits the clinical usefulness of OCTA in populations with cataract, macular lesions, and advanced glaucoma.…”
Section: Resultsmentioning
confidence: 99%
“…In eyes with glaucoma and a single-hemifield defect, diminished vascular density of the macular and peripapillary regions was also demonstrated in unaffected hemifields (41). OCTA of eyes with glaucoma and LC defects portrayed diminished vascular density corresponding to the locations of these defects (42). …”
Section: Novel Oct Technologies and Applicationsmentioning
confidence: 99%
“…Interes ngly, however, the prevalence of DH was similar in the groups with (4/41) and without (7/41) lamina cribrosa defects in their study. 42 AUCs of structural parameters (rim area, RNFL and GCC thickness) were signifi cantly greater (p<0.05 for all comparisons) than that of the vessel density measurements in the ONH, peripapillary and the macular regions both in POAG eyes with and without DH. This may suggest that structural changes occur before vessel density changes in POAG.…”
Section: Discussionmentioning
confidence: 82%
“…They found that in eyes with similar visual sensi vity loss, the decrease in vessel density in POAG eyes with focal lamina cribrosa defects was signifi cantly greater than in POAG eyes without focal lamina cribrosa defects. 42 Because of the strong concordance between DH and lamina cribrosa defects, this result would suggest that the decrease in vessel densi es in POAG eyes with DH would also be greater than in POAG eyes without DH. Interes ngly, however, the prevalence of DH was similar in the groups with (4/41) and without (7/41) lamina cribrosa defects in their study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation